Reciprocal Amplification of Glial Senescence and \(α\)-synucleinopathy in Parkinson’s Disease: The Therapeutic Potential Promise of Senolytics - Audrey Gibbs; Sean J. Miller; Robert Logan (Disease and Health Research: New Insights Vol. 11, 2024)
Parkinson’s disease (PD) is the most common movement disorder and the second most prevalent neurodegenerative disease after Alzheimer’s disease. Despite decades of research, there is still no cure for PD and the complicated intricacies of the pathology are still being worked out. A hallmark of the disease is the abnormal formation of toxic fibrils of \(α\)-synuclein, which then clump into Lewy body aggregates. Lewy bodies rob neurons and glia of their function, eventually leading to their death. This chapter presents a current perspective on the interactive roles that \(α\)-synuclein and glial senescence have in PD. The self-amplifying and cyclical nature of oxidative stress, neuroinflammation, \(α\)-synucleinopathy, neuroglial senescence, neuroglial chronic activation and neurodegeneration will be discussed. This progressive, degenerative cycle can be interrupted by using senolytics to specifically target and remove senescent cells. Therefore, the compelling role that senolytics could play as a therapeutic avenue for PD will also be explored and encouraged.